2016
DOI: 10.1186/s40064-016-3532-3
|View full text |Cite
|
Sign up to set email alerts
|

Problem/case-based learning with competition introduced in severe infection education: an exploratory study

Abstract: BackgroundProblem/case-based learning (PCBL) is one of the most commonly used educational methods in medical schools.AimTo further improve PCBL in clinical course of severe infection by introducing competition mode.MethodsTwo classes of medical students were divided into two groups by class-based simple randomization and were taught the course of severe infection by PCBL. A team-based competition was introduced in the study group (n = 35) while not in the control group (n = 36). After the course, four closely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 20 publications
(20 reference statements)
0
27
0
1
Order By: Relevance
“…Carroll (2013) confirmed that the competition drastically increases the excitement and anticipation of the students. Lei et al (2016) confirmed that competition adopted in learning effectively guides the students to fully understand the concepts and processes with sufficient competency makes them participate in group-consultation. Vandercruysse et al (2013) demonstrated that though the competition is not very much related to students' learning, enriches their skills and capabilities and make the students to perceive the environment as a learning environment.…”
Section: Review Of Literaturementioning
confidence: 67%
“…Carroll (2013) confirmed that the competition drastically increases the excitement and anticipation of the students. Lei et al (2016) confirmed that competition adopted in learning effectively guides the students to fully understand the concepts and processes with sufficient competency makes them participate in group-consultation. Vandercruysse et al (2013) demonstrated that though the competition is not very much related to students' learning, enriches their skills and capabilities and make the students to perceive the environment as a learning environment.…”
Section: Review Of Literaturementioning
confidence: 67%
“…7,9 A study conducted by Lei illustrated that the students educated by PCBL with competition mode were more likely to refer case-related articles and attend group consultation; they also performed better in the final written examination on the clinical diagnoses and treatment of severe infection. 7 Carrero carried out a study on teaching pre-anesthetic assessment in a resident medical training program in Spain, which concluded that the PCBL appeared to be more effective than the LBL in reasoning choice of anesthetic technique. However, the performances of lecture-based and case/problem-based learning mode had little differences in improving residents' immediate pre-anaesthetic assessment knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data regarding learning outcomes comparing PCBL to lecture format show either similar or improved outcomes with LBL format. 7,8 In the study of Aljarallah and Hassan, PCBL showed some other benefits, including improving learning abilities, promoting self-assessment and logical thinking, integrating theory with practice, and encouraging students' personalized learning. 8 Certainly, several studies had different results when comparing these two methods, which may because of the bias between the intervention and control groups, as well as the lecturer and tutor were not identical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research studies have also found that CBL when coupled with other techniques such as cooperative learning (Rodriguez-Sanchez, Torrado-Carvajal, Vaquero, Borromeo, & Hernandez-Tamames, 2016), competition (Lei et al, 2016), and group discussion (Cam & Geban, 2011;Flynn & Klein, 2001) can enhance the benefits of CBL. Rodriguez-Sanchez et al (2016) utilized project-based learning plus peer review meetings to improve CBL.…”
Section: Literature Reviewmentioning
confidence: 99%